(untitled) (Bulletin of Pure and Applied Sciences – Physics, 2020)
We have studied and determined the intrinsic mobility by acoustic phonon scattering which provided on important upper limit for the available motilities. In the low temperature regime, acoustic phonon dominated transport manifested itself in a strong change in the temperature dependence of the carrier mobility once the temperature is lowered below the Bloch Gruneisen temperature. For Hetrostructure based two dimensional electron gas the Bloch Gruneisen regime was well established. In a two dimensional electron gas the Fermi wave vector scales with the carrier density and the Bloch-Gruneisen temperature required density dependence. At low temperature where optical phonon scattering is suppressed, scattering by acoustic phonons become an important limiting factor for the mobility of the two dimensional electron gas confined to the atomic layer of the extrinsic two dimensional semiconductors. We have studied the acoustic phonon limited mobility of n-type semiconductor at low temperatures taking into account both deformation potential and piezoelectric scattering. We have calculated the deformation potential and piezoelectric interactions in two dimensional semiconductors. Supported by continuum model calculations of the acoustic electron-phonon interaction in two dimensional hexagonal lattices, this allowed establishing analytic expressions and the individual coupling strengths for the two scattering mechanisms. The calculated intrinsic low temperature mobility provided a platform for comparison with future measurements of the carrier mobility in monolayer semiconducting compound. We have found that mobility increased monotonically with carrier density. We have found that mobility is substantially higher and showed much richer temperature dependence with higher values of variation factor  and no linear temperature dependence. Our finding for the acoustic electron-phonon interaction is also relevant in semiconductors. The obtained results were found in good agreement with previously results.